The achievement of lap weld and gap control for laser impact welding with water as the confinement layer. (9th June 2023) - Wang, Qihan; Wang, Huimin; Ran, Minrui; Tong, Zhi; Wang, Rui; Zheng, Wenyue
Abstract: Laser impact welding (LIW) with water as the confinement layer is investigated for the first time to join aluminum (Al) and titanium (Ti). A series of experiments of spot welding under different energies and lap welding were carried out. Both spot welds and lap welds were achieved, which is a significant progress in LIW, especially for the lap weld which hasn't been accomplished by means of LIW previously. Another advantage with water as the confinement layer is that it can control the central gap and create the intimate contact between the flyer and the target, that may favor the weld area increase with the subsequent post weld heat treatment for the intense interfacial diffusion. The interfacial interaction mechanism between the flyer and the target in the close intimate contact area was revealed with the substrate stretching test and energy dispersive spectroscopy (EDS) test. The characteristics of the welds, like wave length, wave height and weld area are also quantified to provide detailed information. Our findings in this work reveal the feasibility and advantages of using flexible media for confinement, broadening the application range of LIW in dissimilar materials joining. Highlights: Both lap welds and spot welds were achieved by laser impact welding, which broadens its application in joining. The central gap between a flyer and a target, an undesired phenomenon, was controlled with water as the confinement layer. The interfacial interaction in the intimate contact area of the weld nugget involves mechanical locking and diffusion.